A Dataset of Electrical Components for Mesh Segmentation and Computational Geometry Research - Scheffler, Benedikt; Bründl, Patrick; Nguyen, Huong Giang; Stoidner, Micha; Franke, Jörg (Scientific Data, 2024)
Data quality is of crucial importance in the field of automated or digitally assisted assembly. This paper presents a comprehensive data set of triangle meshes representing electrical and electronic components obtained by scraping Computer Aided Design (CAD) models from the Internet. Consisting of a total of 234 triangle meshes with labelled vertices, this data set was specifically created for segmentation tasks. Its versatility for multimodal tasks is underscored by the presence of various labels, including vertex labels, categories, and subcategories. This paper presents the data set and provides a thorough statistical analysis, including measures of shape, size, distribution, and inter-rater reliability. In addition, the paper suggests several approaches for using the data set, considering its multimodal characteristics. The data set and related findings presented in this paper are intended to encourage further research and advancement in the field of manufacturing automation, specifically spatial assembly.<br
Keywords: Electrical and electronic engineering; Mechanical engineering; Scientific data

Challenges and Opportunities of Software-Based Production Planning and Control for Engineer-to-Order Manufacturing - Bründl, Patrick; Stoidner, Micha; Nguyen, Huong Giang; Baechler, Andreas; Franke, Jörg (Advances in Production Management Systems. Production Management Systems for Responsible Manufacturing, Service, and Logistics Futures. APMS 2023, 2023)
This article aims to explore the use and implementation of software-based production planning and control (PPC) systems in variant-rich manufacturing environments, specifically in the engineer-to-order (ETO) manufacturing. A systematic literature review is conducted to identify, which PPC tools are used in the ETO business, how they should be implemented and the benefits and challenges associated with their use. The results indicate that such systems can be technically and economically advantageous, however application of existing systems off-the shelf solutions is not recommended. The literature suggests a structured approach for the implementation considering critical success factors and a well-planned process supported by the proposed framework. Most of the systems analyzed in the literature are Enterprise Resource Planning systems. Furthermore, the findings show four different areas of positive effects for the companies, such as improved production efficiency, improved planning efficiency, improved decision-making, and increased competitiveness. Additionally, five different kinds of challenges can be observed: Knowledge and expertise, Cost and resource management, Process and system flexibility, Data management and IT infrastructure and System usability and applicability.<br
Keywords: Engineer-to-Order; Production planning and control; Systematic literature review; Implementation guidelines

Designing Manual Workplace Systems in Engineer-to-Order Enterprises to Improve Productivity: A Kano Analysis - Stoidner, Micha; Bründl, Patrick; Matthes, Tina; Nguyen, Huong Giang; Abrass, Ahmad; Franke, Jörg (SAE International Journal of Materials and Manufacturing, 2024)
Being an engineer-to-order (ETO) operating industry, the control cabinet industry faces difficulties in process and workplace optimizations due to changing requirements and lot size one combined with volatile orders. To optimize workplaces for employees, current literature is focusing on ergonomic designs, providing frameworks to analyze workplaces, leaving out the optimal design for productivity. This work thus utilizes a Kano analysis, collecting empirical data to identify essential design requirements for assembly workplaces, incorporating input from switchgear manufacturing employees. The results emphasize the need for a balance between ergonomics and efficiency in workplace design. Surprisingly, few participants agree on the correlation between improved processes and workspaces having a positive impact on their well-being and product quality. Ultimately, the study offers a list of requirements that are needed at ETO assembly stations to satisfy employees and improve efficiency of the production processes.<br
Keywords: Aerospace; Automotive; Commercial Vehicle; Optimization; Productivity; Personnel; Design processes; Supply chain management; Ergonomics; Production; Product development

Digitalization and Adoption of Industry 4.0 in Engineer-to-order Small and Medium-sized Manufacturing Companies: An Empirical Analysis - Bründl, Patrick; Stoidner, Micha; Nguyen, Huong Giang; Baechler, Andreas; Franke, Jörg (2023 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2023)
Industry 4.0 marks a significant shift in manufacturing practices, deeply influencing small and medium-sized enterprises (SMEs) in the engineer-to-order (ETO) sector. This study delves into the impact of digitalization and Industry 4.0 adoption in ETO SMEs, specifically within control cabinet manufacturing. A web-based survey was conducted to explore perceptions of digitalization, perceived advantages, and implementation obstacles of 14.0. Results indicate that ETO SMEs generally perceive digitalization as an opportunity for growth and transformation, expecting notable benefits such as increased efficiency, improved data management, and enhanced product quality. Yet, the study also identified obstacles such as high costs, lack of technical expertise, and cybersecurity concerns. This paper underscores the transformative potential of digitalization and I4.0 within the ETO manufacturing sector, stressing the need for comprehensive support systems and educational initiatives to help SMEs navigate the digital transition, enhance their competitiveness, and ensure their sustain ability in the I4.0 era.<br
Keywords: Costs; Navigation; Product design; Fourth Industrial Revolution; Quality assessment; Computer security; Business; Control cabinet; Digitalization; Engineer-to-Order; Information technology; Industry 4.0; Small and medium-sized enterprises

Optimization of Process, Knowledge, and Manufacturing Management in Customized Production: A Graph-Based Approach for Manufacturing Planning - Bründl, Patrick; Stoidner, Micha; Nguyen, Huong Giang; Abrass, Ahmad; Franke, Jörg (IFAC-PapersOnLine, 2024)
This research paper describes the design and implementation of a graph-based database using Neo4J, specifically tailored to optimize process, knowledge, and manufacturing management in the custom manufacturing environment of control cabinet manufacturing. Given the challenges of digital transformation and increasing data complexity, traditional database systems often fall short in terms of scalability, flexibility, and visualization. This study addresses these gaps by leveraging the capabilities of graph databases. The paper presents a systematic methodology that includes abstraction, data preparation, integration, analysis, and validation against real-world parts lists. The research underscores the potential of graph databases to improve decision-making, streamline workflows, and maximize data-driven resources in an industry characterized by diverse production requirements without excessive manual data generation and management.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Control Cabinet; Engineer-To-order Production; Graph-Based Database; Knowledge Management; Manufacturing Execution System; Process Optimization

Optimizing Intralogistics in an Engineer-to-Order Enterprise with Job Shop Production: A Case Study of the Control Cabinet Manufacturing - Bründl, Patrick; Stoidner, Micha; Nguyen, Huong Giang; Abrass, Ahmad; Franke, Jörg (SAE International Journal of Materials and Manufacturing, 2024)
This study underscores the benefits of refining the intralogistics process for small- to medium-sized manufacturing businesses (SMEs) in the engineer-to-order (ETO) sector, which relies heavily on manual tasks. Based on industrial visits and primary data from six SMEs, a new intralogistics concept and process was formulated. This approach enhances the value-added time of manufacturing workers while also facilitating complete digital integration as well as improving transparency and traceability. A practical application of this method in a company lead to cutting its lead time by roughly 11.3%. Additionally, improved oversight pinpointed excess inventory, resulting in advantages such as reduced capital needs and storage requirements. Anticipated future enhancements include better efficiency from more experienced warehouse staff and streamlined picking methods. Further, digital advancements hold promise for cost reductions in administrative and supportive roles.<br
Keywords: Aerospace; Automotive; Commercial Vehicle; Research and development; Production; Logistics; Traceability; Storage; Materials handling; Cutting; Optimization; Personnel; Supply chain management

Semantic part segmentation of spatial features via geometric deep learning for automated control cabinet assembly - Bründl, Patrick; Scheffler, Benedikt; Stoidner, Micha; Nguyen, Huong Giang; Baechler, Andreas; Abrass, Ahmad; Franke, Jörg (Journal of Intelligent Manufacturing, 2023)
Industries with batch size one manufacturing philosophies for highly customized products have been largely limited in manufacturing automation. The control cabinet industry is particularly affected by this problem during the mounting and wiring of components due to high variety, variance, and complexity of components as well as handling tasks. Rapid advances in the field of machine learning are opening new possibilities for automating previously manual processes. This paper proposes a concept for identifying geometric features of electrical components that starts from STEP files and transforms them into modular metrics relevant to build a digital twin and (automatic)manufacturing. The architecture is tested on a self-aggregated and processed dataset of control cabinet components and achieves an average dice score of 65.27% and an intersection over union of 51.41% across all segmentation classes. In addition to semantic part segmentation of the components, the cluster, volume and surface centroids, the normal vectors and the size of each feature are computed. The paper evaluates the suitability of cutting-edge techniques such as diffusion as well as established deep learning architectures. The result is a hybrid end-to-end inference pipeline suitable for general spatial assembly processes.
Created from Fastlane, Scopus look-up
Keywords: Control cabinet; Digital twin; Geometric deep learning; Semantic part segmentation; Surface mesh processing

Standardizing Process Optimization for Production Processes in the Control Cabinet Industry: A Multiple Case Study - Stoidner, Micha; Bründl, Patrick; Nguyen, Huong Giang; Baechler, Andreas; Franke, Jörg (2023 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2023)
This paper presents a multiple-case study that aims to standardize process improvement in the control cabinet industry and identify areas requiring significant enhancements. The study provides a comprehensive understanding of observed processes, facilitating efficient process design and waste identification. A standardized process survey is developed and applied to a third control cabinet manufacturing company for validation. The findings reveal limited coverage of the control cabinet industry in existing studies. Eleven challenges faced by control cabinet manufacturing companies are identified, including a shortage of skilled workers and limited space. The analysis highlights low evaluations in all seven fields of action. Recommendations include implementing material flow to improve efficiency and identify bottlenecks. The study introduces a systematic analysis framework for evaluating production sites in the control cabinet industry, contributing to operations research and practical applications. It offers a comprehensive framework for analyzing and optimizing control cabinet production processes. Future research should focus on assessing applicability to small and medium-sized enterprises in other industries with similar inefficiencies.<br
Keywords: Industries; Surveys; Systematics; Operations research; Process control; Production; Companies; Control Cabinet Manufacturing; Process optimization; Process recording; Multiple Case Study

Towards a Reconfigurable Manufacturing System for Control Cabinet Manufacturing: A Systematic Literature Review and Research Agenda - Stoidner, Micha; Bründl, Patrick; Nguyen, Huong Giang; Abrass, Ahmad; Franke, Jörg (2024 32nd Mediterranean Conference on Control and Automation (MED), 2024)
In response to the challenges of Industry 4.0 and global competition, this study introduces a research agenda towards an innovative concept for automation tailored to small and medium-sized enterprises (SMEs) in the control and switchgear manufacturing sector. These companies, crucial to machinery and plant engineering industries, face the dilemma of needing increased product customization and shorter delivery times without sacrificing quality, despite cost pressures and a shortage of skilled workers. The proposed solution is outlined based on a systematic literature review on Reconfigurable Manufacturing Systems (RMS) and aims to automate a wide range of manual manufacturing and assembly steps, making it a feasible option for SMEs to adopt manufacturing automation economically. The technical and economic requirements of the control and switchgear cabinet production process chain were analyzed, leading to the conceptualization of a system that significantly reduces lead times and manufacturing times by up to 30 % and 60 %, respectively. Further research needs to validate the possible savings and further detail the functional modules of the concept. Working towards this research goal will not only enhance operational efficiency and competitiveness for SMEs in control cabinet production but will also take a significant step towards industrialization and digitalization in high-wage countries.<br
Keywords: Systematics; Switchgear; Bibliographies; Process control; Production; Companies; Control systems

Towards a Time Data Library to Enable Process Optimization in Engineer-To-Order Industries: The Case of Control and Switchgear Manufacturing - Stoidner, Micha; Bründl, Patrick; Nguyen, Huong Giang; Abrass, Ahmad; Franke, Jörg (IFAC-PapersOnLine, 2024)
This study addresses the crucial role of Time Data Management (TDM) in switchgear and control cabinet manufacturing, sectors integral to industrial automation and characterized by custom-made or small-batch production. The research highlights the challenges in accurately forecasting production times in these domains, where products often have unique, non-repetitive characteristics. This study systematically categorizes production to ensure precise TD collection and analysis. A possible approach to logically divide control cabinet production into distinct manufacturing areas and workflow structures is presented, facilitating a multiple case study method and a comparative TD analysis across different companies. The contribution of this study is threefold: providing detailed workflow structures for an under-researched industry, offering empirical data for academic and practical assessment, and enabling efficient TDM in ETO industries, traditionally hampered by process measurement difficulties and reliance on expert time estimates. This research promises significant advancements in TDM, ensuring more accurate production planning, and cost calculation, and enhancing market competitiveness in switchgear and control cabinet manufacturing.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Control; Engineer-To-Order Production; High-Mix; Low-Volume; Switchgear Cabinet; Time Data Collection; Time Data Management; Workflow Structures

Towards the Digital Factory Twin in Engineer-to-Order Industries: A Focus on Control Cabinet Manufacturing - Stoidner, Micha; Bründl, Patrick; Nguyen, Huong Giang; Baechler, Andreas; Franke, Jörg (Advances in Production Management Systems. Production Management Systems for Responsible Manufacturing, Service, and Logistics Futures, 2023)
Digital transformation poses a challenge for small and medium-sized enterprises (SMEs) with an Engineer-to-Order (ETO) production characterized by a low-variant and low-volume manufacturing philosophy. This article aims to examine the role of a digital factory twin and material flow simulation to increase value creation in ETO production. The study follows a structured approach including a literature review, on-site process analysis, and simulations to determine the optimal production process design. The focus of qualitative and quantitative findings is on the control cabinet manufacturing as an important sector in Germany representative for ETO production. The findings comprise a novel definition of the digital factory twin (DFT), implementation of a simulation model and integration of lean manufacturing principles to optimize ETO production of control cabinets. This study makes a valuable contribution to the development of the DFT and illustrates the successful implementation of simulation as well as lean manufacturing principles.<br
Keywords: Control Cabinet; Digital Factory Twin; Engineer-to-Order; Material Flow Simulation

Traceability in Engineer-to-Order Manufacturing SMEs - Bründl, Patrick; Stoidner, Micha; Nguyen, Huong Giang; Abrass, Ahmad; Franke, Jörg (2024 32nd Mediterranean Conference on Control and Automation (MED), 2024)
This paper examines the implementation and impact of component traceability within small and medium-sized enterprises (SMEs) in the control cabinet manufacturing industry. Through a detailed examination of expert interviews, this study addresses four critical research questions regarding the current state of traceability practices, motivational factors for implementation, challenges faced by companies, and the expected impact on selected business criteria. Our findings reveal a diverse landscape of traceability implementation among the SMEs surveyed. The primary motivators for adopting traceability include quality assurance and defect analysis, customer requirements and regulatory compliance, and product and warranty liability, highlighting the intrinsic and extrinsic factors that drive companies to adopt traceability practices. Conversely, significant barriers preventing SMEs from implementing traceability were identified, including cost-benefit considerations, administrative burden, IT infrastructure challenges, employee resistance to change, and the complexity of managing a diverse range of items and suppliers. The impact of traceability on quality, time-to-market, competitiveness, customer satisfaction, product cost and other business processes was also assessed. In addition, the study highlights the potential for traceability to indirectly impact product costs and facilitate improvements in other operational areas through the strategic use of collected data. This research contributes to a deeper understanding of component traceability in the control cabinet manufacturing sector and provides valuable insights for SMEs considering the implementation and optimization of traceability systems within their operations.<br
Keywords: Resistance; Warranties; Costs; Quality assurance; Automation; Face recognition; Customer satisfaction

Unlocking the potential of digitalization and automation: a qualitative and quantitative study of the control cabinet manufacturing industry - Bründl, Patrick; Stoidner, Micha; Bredthauer, Jens; Nguyen, Huong Giang; Baechler, Andreas; Franke, Jörg (Production & Manufacturing Research, 2024)
This paper investigates the German control cabinet manufacturing industry, revealing its opportunities, challenges, and varying levels of digitalization and automation. The researchers employ cluster analysis, grouping companies into five clusters based on digitalization and automation, resulting in a new classification framework. This framework significantly improves the similarity level within each cluster by approximately 52.89 % compared to pre-existing models. While the levels of digitalization and automation vary greatly between the different clusters, skill shortages and supply chain problems are identified as potential development barriers to companies from all groups. To overcome these obstacles, the paper outlines key improvement areas based on data findings. This proposed classification can guide companies in assessing their digital maturity and pinpointing enhancement areas, emphasizing the necessity of adopting digitalization and automation for improved efficiency and market competitiveness.<br
CRIS-Team Scopus Importer:2024-02-02
Keywords: Control cabinet; digitalization; production automation; production strategies; engineer-to-order production

Workplace Analysis and Ergonomics in Engineer-to-Order Production Sites: A Study on the Workplace Design of Control Cabinet Manufacturing Enterprises - Stoidner, Micha; Bründl, Patrick; Nguyen, Huong Giang; Baechler, Andreas; Franke, Jörg (2023 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2023)
Ergonomic measures aimed at redesigning the workplace and processes are necessary to improve safety, health, and productivity. Work-related musculoskeletal disorders are a major cause of lost productivity and sick leave among workers in the European Union, with the manufacturing sector in Germany having the second highest levels in 2020. The most affected occupational group is machine operators and assemblers. This paper aims to visualize the current state of ergonomics at manual workplaces in engineer-to-order (ETO) companies. The contribution is twofold offering an adapted guideline with criteria for workplace assessment in ETO companies as well as minimum ergonomic requirements for manual workplaces. The requirements were developed based on empirical data collected in three ETO companies, specifically in the use case of control cabinet manufacturing. The findings show that the developed guideline aids managers in purposefully identifying optimization potentials at workspaces and reducing economic losses caused by working conditions.<br
Keywords: Employee welfare; Productivity; Ergonomics; Employment; Sociology; Companies; Manuals; Control Cabinet; Engineer-to-Order; Ergonomic; Workplace Design